Taxation and Leverage in International Banking - Gu, Grace Weishi; Mooij, Ruud A.; Poghosyan, Tigran (Washington, D.C. : International Monetary Fund, 2012)
This paper explores how corporate taxes affect the financial structure of multinational banks. Guided by a simple theory of optimal capital structure it tests (i) whether corporate taxes induce subsidiary banks to raise their debt-asset ratio in light of the traditional debt bias; and (ii) whether international corporate tax differentials vis-a-vis foreign subsidiary banks affect the intra-bank capital structure through international debt shifting. Using a novel subsidiary-level dataset for 558 commercial bank subsidiaries of the 86 largest multinational banks in the world, we find that taxes matter significantly, through both the traditional debt bias channel and the international debt shifting that is due to the international tax differentials. The latter channel is more robust and tends to be quantitatively more important. Our results imply that taxation causes significant international debt spillovers through multinational banks, which has potentially important implications for tax policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet